Manganese/iron‐supported sulfate‐dependent anaerobic oxidation of methane by archaea in lake sediments - Su, Guangyi; Zopfi, Jakob; Yao, Haoyi; Steinle, Lea; Niemann, Helge; Lehmann, Moritz F (Limnology and Oceanography, 2019)
Anaerobic oxidation of methane (AOM) by methanotrophic archaea is an important sink of this greenhouse gas in marine sediments. However, evidence for AOM in freshwater habitats is rare, and little is known about the pathways, electron acceptors, and microbes involved. Here, we show that AOM occurs in anoxic sediments of a sulfate‐rich lake in southern Switzerland (Lake Cadagno). Combined AOM‐rate and 16S rRNA gene‐sequencing data suggest that Candidatus Methanoperedens archaea are responsible for the observed methane oxidation. Members of the Methanoperedenaceae family were previously reported to conduct nitrate‐ or iron/manganese‐dependent AOM. However, we demonstrate for the first time that the methanotrophic archaea do not necessarily rely upon these oxidants as terminal electron acceptors directly, but mainly perform canonical sulfate‐dependent AOM, which under sulfate‐starved conditions can be supported by metal (Mn, Fe) oxides through oxidation of reduced sulfur species to sulfate. The correspondence of high abundances of Desulfobulbaceae and Candidatus Methanoperedens at the same sediment depth confirms the interdependence of anaerobic methane‐oxidizing archaea and sulfate‐reducing bacteria. The relatively high abundance and widespread distribution of Candidatus Methanoperedens in lake sediments highlight their potentially important role in mitigating methane emissions from terrestrial freshwater environments to the atmosphere, analogous to ANME‐1, ‐2, and ‐3 in marine settings.